AN ANALYSIS OF PRE-SERVICE TEACHERS’ ANXIETY IN TEACHING ELT STUDENTS AT IAI AL-QOLAM - MARIA ULFA; HANIF MAULANIAM SHOLAH (IAI Al-Qolam, 2023)
The purpose of this study was to determine the level of speaking anxiety of pre-service teacher English, avoid anxiety by knowing the causes and overcome anxiety in learning in the classroom. This research uses descriptive qualitative research. The subjects of this study were 15 students of IAI Al- Qolam who had already Experience Practice. Data is taken from questionnaires and interviews where the questionnaire consists of 10 questions with 4 choices, namely agree, strongly agree, disagree and strongly disagree to find out the level of anxiety of pre-service teacher English. Based on the results of the study, it can be said that the factors that influence the anxiety level of pre-service teacher students are that of the fifteen subjects, data is obtained. The influencing factors are the lack of vocabulary, low self-confidence and lack of teaching experience. The impact of teacher candidates' speaking anxiety is a lack of confidence in teaching, finding it difficult to concentrate and a lack of interaction with students. Strategies for overcoming teacher candidates' speaking anxiety are to prepare well, study teaching materials carefully, improve English skills, practice the material to be taught, ask for support from colleagues and school staff so they can share experiences and evaluate. Keywords: Impact, Anxiety, Speaking Anxiety, Factors, pre-service teachers